Increasing Children's Interest in Learning the Qur’an Through a Creative TPQ Educational Program at Al-Mubaarak Mosque, Bengkulu City - Cinta Septiana; Defi Zaina Putri; Rihelvia Apriani; Yolanda Wansari; Salamah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The Creative TPQ Education Program was implemented at TPQ Masjid Al-Mubaarak, Sumur Dewa Village, Selebar District, Bengkulu City, to improve children's interest in learning the Qur’an. The program was motivated by several problems identified during the initial observation, including low student attendance, limited variation in teaching methods, minimal use of educational media, and low participation and enthusiasm among students during learning activities. On the other hand, the TPQ possessed valuable assets that could be utilized, such as adequate mosque facilities, support from TPQ administrators and parents, a considerable number of students, and children's enthusiasm for creative and interactive activities. This community service activity aimed to increase students’ interest in learning the Qur’an, participation, and engagement through enjoyable and innovative learning approaches. The method employed was the Asset Based Community Development (ABCD) approach, consisting of four stages: discovery, dream, design, and destiny. The program activities included Qur’an reading assistance, Islamic educational games, short surah memorization competitions, and Islamic calligraphy coloring contests. The results showed improvements in student attendance, participation, Qur’an reading skills, memorization of short surahs, and enthusiasm for attending TPQ activities. In addition, the program enhanced students’ creativity and self-confidence. Therefore, the Creative TPQ Education Program proved effective in creating an interactive and enjoyable learning environment that supports the sustainable improvement of children's interest in learning the Qur’an.